Pemanfaatan Pembenah Tanah dan Mikroba Pelarut P untuk Meningkatkan Efektivitas Pupuk NPK pada Usahatani Jagung di Lahan Kering Masam - Soelaeman, Yoyo; Maswar, Maswar; Haryati, Umi (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Maize farming on an acid upland soil generally gives high priority to the use of chemical/NPK fertilizers. Application of organic soil amendments and P (phosphate) solubilizing microbes in maize farming on an acid upland soil were expected to substitute the use of NPK fertilizer without reducing the yields. The research aims was to study the effectiveness of biochar, cow dunk and P solubilizing microbes applications to substitute NPK fertilizers application as shown on the growth and productivity of maize (var. P 27), Relatively Agronomic Effectivenes (RAE) and B/C ratio. The research was conducted from January to June 2014 on an acid upland soil at Tamanbogo Experimental Farm, East Lampung District using randomized block design with four replications. The treatment consisted of Control (T1), NPK fertilizer recommendation dose (T2); biochar 5 t/ha + 50% of NPK recommendation dose (T3); P solubilizing microbes 5 g/plant + 50% of NPK recommendation dose (T4); Cow dunk 5 t/ha + 50% of NPK recommendation dose (T5) and biochar 5 t/ha + P solubilizing microbes of 5 g/plant + cow dunk 5 t/ha + 50% of NPK recommendation dose (T6). The results showed that the combination of NPK fertilizer at a dose of 50% of NPK recommendation + cow dunk at a dose of 5 t/ha (T5), showed the best growth and productivity of P27 maize with B/C ratio of 2.10.